Al-Buti's Thoughts on Maslāhah and Its Application in the Fatwa of World Fatwa Institutions - Dahlan, Abdurrahman; Qodsiyah, Bagus Haziratul; Azizah, Azizah; Asmawi, Asmawi; Hejazziey, Djawahir (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This study aims to explore and analyze al-Buti's thoughts on maslahah (public interest) and its application issued by world-prominent Fatwa Institutions, namely Ḍār al-Iftā al-Miṣriyah in Egypt, Ḍār al-Iftā al-‘Irāqiyah in Iraq, and al-Majlis al-Islamī al-Sūrī in Syria. The research adopts a normative method, employing conceptual, literary, and sociological approaches that is analyzed descriptively. The findings of this research focus on the application of al-Buti's concept of maṣlaḥah to the online marriage contract fatwas issued by the aforementioned Fatwa Institutions. The results indicate that these fatwas do not align with a credible interpretation of maṣlaḥah within Islamic law. Further, it can be seen that two key points support this conclusion: (i) they contradict the maqāṣid sharī'ah (objectives of Islamic law), particularly the highest objective of preserving religion (hiẓ al-dīn), and (ii) the urgency of maṣlaḥah in the context of online marriage contracts varies and cannot be universally applied. This research contributes to the enhancement of fatwa decision-making processes in Indonesia.